The ‘Ivy Sign’ of Moyamoya disease - Karadan, Ummer; Manappallil, Robin George (Asian Journal of Medical Sciences, 2019)
Stroke is uncommon in pediatric age group. Moyamoya is a rare idiopathic disease characterized by progressive vaso-occlusion of the main blood vessels to the brain. We report a case of 13 year old female who presented with recurrent headache and transient left hemiparesis and was diagnosed to have Moyamoya disease. The ‘ivy sign’ is a characteristic magnetic resonance image finding seen in patients with Moyamoya disease.